Karakteristik fisikokimia dan antioksidan garam mandi (bath salt) yang diperkaya tepung Sargassum sp. : Physicochemical and antioxidant characteristics of bath salt enriched with Sargassum sp. flour - Salamah, Zahra Rizki; Sahubawa, Latif; Puspita, Indun Dewi; Putra, Mgs. Muhammad Prima (Jurnal Pengolahan Hasil Perikanan Indonesia, 2025)
Coarse salt and seaweed have various benefits in both food and non-food sectors. The important functions of coarse salt for the skin are maintaining electrolyte balance, detoxification, exfoliation, balancing skin pH, and antibacterial (curing acne) properties. This study aimed to determine the optimal concentration of Sargassum sp. flour in bath salts based on antioxidant activity and solid and liquid bath soap quality standards, and to calculate its economic value. Bath salts were processed by mixing coarse salt, Sargassum sp. seaweed flour, and essential oils. The treatment of adding Sargassum sp. flour was 0 (control), 2, 4, and 6%. The parameters analyzed included moisture content, pH, foam height, dissolution time, antioxidant activity using the DPPH method, sensory attribute profiles using Quantitative Descriptive Analysis (QDA), and economic value. The yield of Sargassum sp. flour (12.5%), and the moisture content (10.39%), and antioxidant activity (33.16%). The average values of the water content of the bath salts (4.10-4.37%); pH (6.31-7.05); foam height (0.13-0.43 cm); dissolving time (1.32-1.44 minutes); and IC50 (100,9214±0,411-261,8415±0,147 ppm). The sensory attributes were as follows: lavender essential oil aroma, eucalyptus oil aroma, mint aroma, dried seaweed aroma, white salt color, rock sugar shine, momogi chocolate, hard texture, coarse salt, sand grains, slippery, and rough. The economic value of bath salts was IDR 92,520 per item. The addition of 6% Sargassum sp. flour produces the best bath salt characteristics based on the quality standards of solid bath soap (SNI 3532: 2021) and liquid bath soap (SNI 06-4085-1996).